Genome-wide association study of periodontal pocketing in Finnish adults - Paula Tegelberg; Jussi Miikkael Leppilahti; Atte Ylöstalo; Tellervo Tervonen; Johannes Kettunen; Anna Liisa Suominen; Pekka Ylöstalo (BMC, 2021)
Abstract Background A genome‐wide association study is an analytical approach that investigates whether genetic variants across the whole genome contribute to disease progression. The aim of this study was to investigate genome-wide associations of periodontal condition measured as deepened periodontal pockets (≥ 4 mm) in Finnish adults. Methods This study was based on the data of the national Health 2000 Survey (BRIF8901) in Finland and the Northern Finland Birth Cohort 1966 Study totalling 3,245 individuals. The genotype data were analyzed using the SNPTEST v.2.4.1. The number of teeth with deepened periodontal pockets (≥ 4 mm deep) was employed as a continuous response variable in additive regression analyses performed separately for the two studies and the results were combined in a meta-analysis applying a fixed effects model. Results Genome-wide significant associations with the number of teeth with ≥ 4 mm deep pockets were not found at the p-level of < 5 × 10−8, while in total 17 loci reached the p-level of 5 × 10−6. Of the top hits, SNP rs4444613 in chromosome 20 showed the strongest association (p = 1.35 × 10−7). Conclusion No statistically significant genome-wide associations with deepened periodontal pockets were found in this study.